Co-operation strategies of Polish companies as a response to foreign investors' expansion into the Polish market - Gorynia, Marian; Jankowska, Barbara; Owczarzak, Radosław (Economics and Business Review, 2005)
The issue of a company's expansion into foreign markets is extensively discussed in specialist literature. What deserves more attention, however, is the perspective of the discourse. The problems of internationalisation at the microeconomic level are usually discussed from the viewpoint of a company which is actively internationalising its activity, while issues directly concerning host-country companies (which face the consequences of such an "invasion") stay in the background. In the present paper, theoretical discussion is exemplified with the results of empirical research conducted in 2004 among 77 Polish companies. The paper focuses primarily on the forms of co-operation between Polish and foreign companies - those which have subsidiaries or branches in the Polish market as well as those which are getting into the market through other forms of internationalisation. (original abstract)